Family and professional pressures of Emirati women and their impact on their political participation in UAE society - Bin Awn, Arwa; Bayoumy, Mohamed (Al-Adab Journal, 2024)
This study purposes to identify the family and professional pressures faced by Emirati women and affected their participation in political and societal life, despite the UAE’s progress in empowering woman and providing them with appropriate opportunities, but they still face challenges in this area, and the study relied on the process of a social survey using a questionnaire, which consists of (16) items, and study population consists of Emirati women of different age, educational and cultural groups.